Impact of IL-12 in Cancer - Lu, Xinjie (Current Cancer Drug Targets, 2017)
Background: Interleukin 12 (IL-12) is a pleiotropic cytokine that plays an essential role in Th1-type immune response against cancer, a condition where cells in a particular part of the body grow and reproduce uncontrollably. Methods: In this review, we describe the structural features of IL-12 family and their roles involved in cancer. Results: IL-12 has been demonstrated to regulate both innate (natural killer cells) and adaptive (cytotoxic T lymphocytes) immunities in cancer therapy. This cytokine has been proposed as a potential new agent to be developed in cancer immunotherapy studies due to its impressive antitumor effects in many animal models. In addition, the antitumor activity of IL-12 can be efficiently induced by itself as well as significantly improved by its combination with various treatment modalities including antibodies, antiangiogenic agents, radiotherapy, adoptive therapy, and anti-tumor vaccines. Conclusion: IL-12 has potential roles in anticancer therapy. The advantages of using immunotherapeutic approaches in clinical trials have been reported recently. However, the mechanisms to underlay the immunoregulation and antitumor activities of IL-12 itself, as well as its combination, remain under investigation.
Keywords: IL-12